Crazy Cupid love - Heger, Amanda (Sourcebooks Casablanca, 2019)
Eliza Herman, a descendant of the Greek god Eros, finds herself working in her family's Cupid-for-hire store, enchanting people looking for love, under the supervision of Jake Sanders, whom she had a crush on as a teenager.